Drones as a support tool for seismic acquisition. Issue 1 (1st December 2019) - Stephenson, Jason; Strong, Shaun
Summary: The availability of relatively inexpensive UAVs in the form of drones provides many opportunities to seismic exploration. While government regulations still provide many restrictions in this space, this trial has demonstrated that significant advantage can be achieved by using these tools. These have the potential to improve the safety of personnel and reduce the QC costs of seismic acquisition.